Führt das Verursacherprinzip zu einer Mehrbelastung für den Straßenverkehr? - Hirte, Georg (DVV Media Group, 2009)
Eine durch die EU-Kommission angestrebte Einführung des Verursacherprinzip zielt darauf ab, soziale Kosten des Verkehrs zu internalisieren. Erst seit kurzem wird intensiver diskutiert, welche Folgen sich daraus hinsichtlich der finanziellen Belastung des Straßenverkehrs ergeben müssten. Diese hängen unter anderem davon ab, wie hoch die verursachten sozialen Zusatzkosten in Form von externen Kosten, externen Staukosten und Infrastrukturkosten sind. Entsprechende Rechnungen werden im Beitrag präsentiert.

It has been the EU Commission's long term intention to adopt the perpetrator principle for the purpose of internalizing the social cost element in transport. Of late, more intensive discussions have focused on the impact of such a financial burden on road traffic, since the level of any additional social costs depends on external costs generally, external costs generated by traffic jams or hold-ups and infrastructure-related costs. Relevant cost estimates are presented below, which help to create awareness of the problems caused by any divergence of social from private costs. The financial impact is dependent on whether the contributions already made by road traffic actually cover a part of the intended cost internalization or whether they could be lowered to compensate road traffic for the adoption of the polluter principle. These aspects are being discussed further on. By taking all the alternatives into account, it can be expected that the adoption of polluter pays principle will increase the financial burden on road traffic.
Will the adoption of the polluter pays principle prompt an increase in the financial burden on road traffic?
Keywords: Verkehr; Straßenverkehr; Verkehrswegefinanzierung; Personenverkehr; Individualverkehr; Güterverkehr; Steuer; Kostenrechnung; Berechnung; Verursacherprinzip; Verkehrskosten; Verkehrsabgabe; Internalisierung